The role of meditation in coping with stress during the COVID-19 lockdown: a cross-sectional study of undergraduates in India - Munjal, Puja; Khurana, Neetika; Saggar, Manish; Kumar, Lalit (Frontiers in Psychiatry, 2025)
BackgroundThe COVID-19 pandemic significantly impacted mental health worldwide, particularly among college students. This study aimed to evaluate the effects of regular meditation practice on stress and well-being during the COVID-19 lockdown in college students from Delhi, India.MethodsData were collected from April 22 to June 3, 2020. Participants included college students aged 18–26, divided into two groups: those with regular meditation practice and those without prior meditation experience. Stress levels were measured using the Perceived Stress Scale (PSS-10). Statistical analyses included group comparisons and regression models to examine the relationship between meditation frequency, duration, and stress levels.ResultsCompared to the meditation-naive group, participants in the meditation group reported significantly fewer adverse effects of the lockdown on their mental and emotional well-being. Stress levels were lower in the meditation group, and both the frequency and duration of meditation sessions were inversely associated with stress.ConclusionsRegular meditation practice appears to mitigate the negative impact of lockdown on mental health, reducing stress and promoting emotional well-being. These findings underscore the potential of meditation as an accessible, effective tool for stress management, particularly in challenging contexts such as the COVID-19 pandemic.